Implikasi Hukum bagi Perusahaan Penanaman Modal Asing di Sektor Pertambangan dalam Melaksanakan Kewajiban Divestasi Saham - Denata, Dicky (UNES Law Review, 2023)
The presence of Law Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining, and Government Regulation Number 96 of 2021 concerning Implementation of Mineral and Coal Mining Business Activities gives a new color to the world of mining stock investment in Indonesia. The change in regulation has caused problems related to disagreements and company disobedience to divestment obligations. This research method is normative juridical so as to produce secondary data that can be analyzed qualitatively. The case study focused on PT Freeport Indonesia's disobedience and disagreement with the obligation to divest shares related to the contract of work which still adheres to past regulations. The shares divestment offer made by the Mining Business Permit and Special Mining Business Permit holders was not achieved due to the uncertainty of the mechanism in the applicable regulations. Legal protection for foreign investment companies in carrying out divestment obligations is needed to build the economy and prosperity of the people in Indonesia.